Mental health stigma among international university students in Malaysia - Kesantini AthinarayananRa; Getrude Cosmas Ah Gang; Carmella Ading (Human Resource Management Academic Research Society (HRMARS), 2025)
This study explored the effects of public stigma and self-stigma on psychological help-seeking attitudes among international university students in Malaysia, guided by the Theory of Planned Behaviour (TPB). A quantitative research design was adopted, and 250 participants were selected using a simple random sampling method from an international university in Malaysia, following ethics approval. Three validated instruments were used: the Perceptions of Stigmatization by Others for Seeking Help (PSOSH), the Self-Stigma of Seeking Help (SSOSH), and the Attitudes Toward Seeking Professional Psychological Help – Short Form (ATSPPH-SF). The findings revealed that self-stigma significantly and negatively accounted for 6% of the variance in students’ psychological help-seeking attitudes, 2 % of the variance in openness to seeking help, and 7 % of the variance in the perceived value of seeking help. Conversely, public stigma did not directly affect help-seeking attitudes, though a significant positive correlation between public stigma and self-stigma suggests an indirect effect through the internalization of stigma. These results highlight the critical role of self-stigma in shaping help-seeking behaviour and underscore the need for culturally sensitive mental health initiatives that address internalized stigma among international students from individualistic cultures in Malaysian universities.